(untitled) (Boletín Epidemiológico Semanal, 2025)
Introduction: Q fever is caused by Coxiella burnetii, a highly infectious and resistant bacterium. Spain notifies the highest number of cases in Europe. Method: A descriptive analysis of autochthonous cases notified to RENAVE in the 2020-2024 period. Variables of person, place and time were analysed by calculating frequencies, percentages and notification rates (NR). Disease maps were generated. Results: In 2024, 544 cases were notified (NR= 1.12), both maximum values for the period 2020-2024. Seasonality shifted, with increased cases in January and February. Andalusia notified the highest number of cases and Navarre the highest NR. Discussion: The increase of cases is likely related to improved disease notification. Men over 45 years old are occupationally at-risk. A One Health approach is recommended.